Identifikasi Faktor Kejadian Penyakit Jantung Koroner Terhadap Wanita Usia ≤ 50 Tahun di RSU Haji Surabaya - Sumara, Retno; Wibowo, Nugroho Ari; Indarti, Indarti (Jurnal Manajemen Asuhan Keperawatan; Vol 6 No 2 (2022): Jurnal Manajemen Asuhan Keperawatan, 2022)
Coronary Heart Disease (CHD) has become the main cause of death in the world and in Indonesia. Many people have heart attacks without any symptoms. Men have a higher risk of developing coronary heart disease sooner than women. Women have a risk of coronary heart disease during menopause. Typical symptoms felt by patients with coronary heart disease are chest pain that radiates to the back, arms, neck. This study aims to identify the risk factors for coronary heart disease in women aged 50 years at RSU Haji Surabaya. The design of descriptive analysis was carried out on all patients with CHD as many as 30 patients with Consecutive Sampling with medical record data instruments (history of hypertension, obesity, cholesterol, smoking and diabetes mellitus). The results showed that CHD in women 50 years was dominantly caused by a history of hypertension 63%, history of high cholesterol and obesity 56.7%, history of DM 43.3%, family history 10%, history of smoking 6.7%. One of the main factors causing CHD is hypertension. Increased pressure of blood vessels against arterial walls can result in endothelial damage that triggers atherosclerosis.